Peran Integrated Reporting dalam Membentuk Persepsi Investor di Pasar Berkembang: Systematic Literature Review - Ririn Nurilah; Yusnaini Yusnaini (Pajak dan Manajemen Keuangan, 2026)
This study examines the strategic role of Integrated Reporting (IR) in shaping investor perceptions in emerging markets, where transparency is essential for investment decision-making amid complex and volatile conditions. Using the Systematic Literature Review (SLR) method with the PRISMA framework, this study ensured objective source selection and rigorous article screening. A total of 119 articles were identified from Scopus and Google Scholar using the keywords “Integrated Reporting,” “Investor Perception,” and “Emerging Markets.” After applying inclusion criteria, 29 relevant articles were selected for analysis. The findings indicate that IR plays a significant role in building positive investor perceptions by reducing information asymmetry, enhancing reporting transparency, and improving the disclosure quality of non-financial information. Investors in emerging markets generally respond positively to IR implementation, particularly when supported by strong corporate governance and clear regulatory frameworks. However, the relationship between IR and investor perception varies across contexts due to differences in institutional environments, regulatory systems, and capital market maturity. This study contributes by mapping IR dynamics in emerging markets and identifying conceptual gaps and implementation challenges for future research and policymaking.